Chronic stress and its effect on brain structure and connectivity - Starcevic, Ana, 1979- (Advances in psychology, mental health, and behavioral studies., 2019)
"This book explores the stress impact of individuals and consequently its impact on the community as a whole. It examines chronic stress impact and influence on different brain structures, its consequences with psychiatric implications, basic and clinical related stress research, stress impact related to different medical conditions, and the treatment and prevention of chronic stress"--Provided by publisher.